EFEKTIVITAS PENGGUNAAN LEMBAR KERJA SISWA BERBASIS KETERAMPILAN PROSES SAINS (KPS) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI - Megawati Megawati; Rahmatsyah Rahmatsyah; Anita Yus (JURNAL TEMATIK, 2020)
This study aims to determine: (1) whether or not there are significant differences in the abilityto think at a higher level between students who are taught with worksheets based on science processskills and students who are taught without using worksheets based on science process skills; (2) theeffectiveness of using student worksheets based on science process skills to improve higher orderthinking skills. This research was conducted in class V of Nurul Hasanah Tembung Private PrimarySchool. This study uses a quantitative approach. This research method is a quasi experiment with theNonequivalent Control Group Design. The population in this study was grade V private primary schoolNurul Hasanah Tembung. The technique to determine the sample is custer sampling namely the VAclass as an experimental class and the VB class as a control class. The validity used is content validityand reliability using Cronbach's Alpha. The analysis technique uses t-test. Based on the calculation ofthe significant value of the Independent sample t test is 0,000 <0.05 and the Ngain Score calculation,the average value of the experimental class is 74.80 with a quite effective category is greater than theaverage value of the control class that is 34.04 with a category ineffective. This shows that the use ofstudent worksheets based on science process skills is very effective for improving higher order thinkingskills